2002
DOI: 10.1021/bi026120w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiviral Evaluation of a Mutagenic and Non-Hydrogen Bonding Ribonucleoside Analogue:  1-β-d-Ribofuranosyl-3-nitropyrrole

Abstract: Synthetic small molecules that promote viral mutagenesis represent a promising new class of antiviral therapeutics. Ribavirin is a broad-spectrum antiviral nucleoside whose antiviral mechanism against RNA viruses likely reflects the ability of this compound to introduce mutations into the viral genome. The mutagenicity of ribavirin results from the incorporation of ribavirin triphosphate opposite both cytidine and uridine in viral RNA. In an effort to identify compounds with mutagenicity greater than that of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 58 publications
1
47
0
Order By: Relevance
“…Despite this, previous attempts to design novel mutagenic nucleotide analogues that are capable of inducing mutation in RNA viruses have had only limited success (17)(18)(19)39). In this study, we have demonstrated that rPTP is an efficient and ambiguous substrate of a viral RNA-dependent RNA polymerase.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Despite this, previous attempts to design novel mutagenic nucleotide analogues that are capable of inducing mutation in RNA viruses have had only limited success (17)(18)(19)39). In this study, we have demonstrated that rPTP is an efficient and ambiguous substrate of a viral RNA-dependent RNA polymerase.…”
Section: Discussionmentioning
confidence: 75%
“…Cells were maintained at 37°C in a 5% CO 2 atmosphere. Antiviral activity assays were performed as previously described (19). A guanidine resistance assay was performed as previously described (7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While both nucleotides reduced the specific infectivity of viral RNA, the responses observed for PV and CVB3 were identical. PMP substitution sufficient for a 10-fold reduction in PV-specific HeLa S3 cells (1 ϫ 10 5 in 24-well plates) were pretreated with ribavirin for 1 h prior to infection with either PV or CVB3 at an MOI of 0.01 (A) or 5 (B) as previously described (17). Cells were incubated with ribavirin at the indicated concentration until all cells demonstrated a cytopathic effect or for 6 days, at which time virus was collected and titers were determined using HeLa S3 monolayers.…”
mentioning
confidence: 99%
“…To examine the biological activity of a triphosphate prepared by this method, we investigated the incorporation of 6-methylpurine ribonucleoside triphosphate (25) into RNA by RNA-dependent RNA polymerase from poliovirus (3D pol ). The cognate ribonucleoside, an antiviral and anticancer agent with activity against RNA viruses, lacks a clearly defined mechanism of action.…”
mentioning
confidence: 99%